Age‐related impairment of endothelial progenitor cell migration correlates with structural alterations of heparan sulfate proteoglycans. Issue 1 (17th January 2013) - Williamson, Kate A.; Hamilton, Andrew; Reynolds, John A.; Sipos, Peter; Crocker, Ian; Stringer, Sally E.; Alexander, Yvonne M.
Summary Aging poses one of the largest risk factors for the development of cardiovascular disease. The increased propensity toward vascular pathology with advancing age maybe explained, in part, by a reduction in the ability of circulating endothelial progenitor cells to contribute to vascular repair and regeneration. Although there is evidence to suggest that colony forming unit‐Hill cells and circulating angiogenic cells are subject to age‐associated changes that impair their function, the impact of aging on human outgrowth endothelial cell (OEC) function has been less studied. We demonstrate that OECs isolated from cord blood or peripheral blood samples from young and old individuals exhibit different characteristics in terms of their migratory capacity. In addition, age‐related structural changes were discovered in OEC heparan sulfate (HS), a glycocalyx component that is essential in many signalling pathways. An age‐associated decline in the migratory response of OECs toward a gradient of VEGF significantly correlated with a reduction in the relative percentage of the trisulfated disaccharide, 2‐O‐sulfated‐uronic acid, N, 6‐O‐sulfated‐glucosamine (UA[2S]‐GlcNS[6S]), within OEC cell surface HS polysaccharide chains. Furthermore, disruption of cell surface HS reduced the migratory response of peripheral blood‐derived OECs isolated from young subjects to levels similar to that observed for OECs from older individuals. Together these findings suggest that aging is associated with alterations in the fine structure of HS on the cell surface of OECs. Such changes may modulate the migration, homing, and engraftment capacity of these repair cells, thereby contributing to the progression of endothelial dysfunction and age‐related vascular pathologies.